Wolność słowa jako narzędzie walki - Martin Jay (Analiza i Egzystencja, 2022)
Recent condemnation by progressive Americans of the conservative “weaponization” of free speech for cynical purposes, while accurate in its accusation of hypocrisy, often assumes a problematic “absolutist” notion of free speech as an inherent good. Instead, it should always be understood as functional in the service of another purpose, whether objective, subjective or intersubjective. Most frequently, it enables the epistemological search for the truth, a function stressed by liberals like J.S. Mill and Marxists like Herbert Marcuse (who argued that this search was hampered by “repressive tolerance” for wrong or evil ideas). It can also be defended for allowing the expression of individual opinions and feelings, which is the inherent mark of personal autonomy. Its third function is performative, the ability of language to make something happen in the world. The most heated current controversy reflecting this function concerns the limiting of offensive “hate speech” for committing symbolic violence, but it can have benign intersubjective effects as well. A fourth purpose of unconstrained speech, more semantic than epistemological, expressive or performative, is the generation of new cultural meanings or the critique of conventional ones. Because it can serve all or any of these functions, it is worth protecting even in an imperfect society, pace Marcuse, despite its lacking an absolute justification in itself.